Same but different: Comparative modes of information processing are implicated in the construction of perceptions of autonomy support - Lee, R.; Chatzisarantis, Nikos (John Wiley & Sons Ltd., 2017)
© 2017 The British Psychological Society.An implicit assumption behind tenets of self-determination theory is that perceptions of autonomy support are a function of absolute modes of information processing. In this study, we examined whether comparative modes of information processing were implicated in the construction of perceptions of autonomy support. In an experimental study, we demonstrated that participants employed comparative modes of information processing in evaluating receipt of small, but not large, amounts of autonomy support. In addition, we found that social comparison processes influenced a number of outcomes that are empirically related to perceived autonomy support such as sense of autonomy, positive affect, perceived usefulness, and effort. Findings shed new light upon the processes underpinning construction of perceptions related to autonomy support and yield new insights into how to increase the predictive validity of models that use autonomy support as a determinant of motivation and psychological well-being.